First investigations to refine video-based IR thermography as a non-invasive tool to monitor the body temperature of calves. (20th July 2015) - Hoffmann, G.; Schmidt, M.; Ammon, C.
Abstract : In this study, a video-based infrared camera (IRC) was investigated as a tool to monitor the body temperature of calves. Body surface temperatures were measured contactless using videos from an IRC fixed at a certain location in the calf feeder. The body surface temperatures were analysed retrospectively at three larger areas: the head area (in front of the forehead), the body area (behind forehead) and the area of the entire animal. The rectal temperature served as a reference temperature and was measured with a digital thermometer at the corresponding time point. A total of nine calves (Holstein-Friesians, 8 to 35 weeks old) were examined. The average maximum temperatures of the area of the entire animal (mean±SD: 37.66±0.90°C) and the head area (37.64±0.86°C) were always higher than that of the body area (36.75±1.06°C). The temperatures of the head area and of the entire animal were very similar. However, the maximum temperatures as measured using IRC increased with an increase in calf rectal temperature. The maximum temperatures of each video picture for the entire visible body area of the calves appeared to be sufficient to measure the superficial body temperature. The advantage of the video-based IRC over conventional IR single-picture cameras is that more than one picture per animal can be analysed in a short period of time. This technique provides more data for analysis. Thus, this system shows potential as an indicator for continuous temperature measurements in calves.